Neuroendocrine Liver Metastasis Treated by Using Intraarterial Therapy: Volumetric Functional Imaging Biomarkers of Early Tumor Response and Survival - Gowdra Halappa, Vivek (Radiological Society of North America, Inc., 2013)
PURPOSE: To determine if volumetric changes of diffusion-weighted and contrast material–enhanced magnetic resonance (MR) imaging can help assess early tumor response to intraarterial therapy (IAT) in neuroendocrine liver metastasis (NELM). MATERIALS AND METHODS: This retrospective single-center comprehensive imaging analysis was performed in compliance with HIPAA and was institutional review board approved. Informed patient consent was waived. Seventy-one patients (39 men; mean age, 62.3 years) with NELM treated with IAT were analyzed retrospectively. MR studies were performed before and 3–4 weeks after therapy. The index lesion was segmented to provide volumetric functional analysis of apparent diffusion coefficient (ADC) and contrast-enhanced MR imaging in the hepatic arterial phase (HAP) and portal venous phase (PVP). Tumor response was defined as increase in volumetric ADC of 15% or greater and decrease in volumetric enhancement of 25% or greater during the HAP or of 50% or greater during the PVP. Patient overall survival was the primary end point after therapy initiation. Univariate analysis included Kaplan-Meier survival curves. The Cox proportional hazards regression model was used to detect interactions between volumetric ADC and contrast-enhanced MR imaging and to calculate the hazard ratio. RESULTS: There was significant increase in mean volumetric ADC (27%, P < .0001) and significant decrease in mean volumetric enhancement during the HAP (−25.3%, P < .0001) and the PVP (−22.4%, P < .0001) in all patients. Patients who had 15% or greater volumetric ADC increase (n = 49) after therapy had better prognosis than those who had less than 15% increase in volumetric ADC (n = 22) (log-rank test, P < .002). Patients who had 25% or greater decrease in volumetric arterial enhancement (n = 40) or 50% or greater decrease in venous enhancement (n = 18) had better prognosis than those who had less than 25% decrease in volumetric arterial enhancement (n = 31) or less than 50% decrease in venous enhancement (n = 53) (log-rank test, P < .02). CONCLUSION: Volumetric functional MR imaging criteria may act as biomarkers of early response, indicating that these criteria may be important to incorporate in future NELM clinical trials. © RSNA, 2012 Supplemental material: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.12120495/-/DC1